Auditor independence: Malaysian accountants’ perceptions - Abu Bakar, Nur Barizah; Ahmad, Maslina (Canadian Center of Science and Education, 2009)
Independence is the primary justification of the existence, and thus the hallmark of the auditing profession. It is recognized as the primary attribute to be maintained by auditors in all circumstances. This study attempts to explore the determinants of auditor independence as perceived by Malaysian accountants using a self-administered mail survey. It was evidenced from the survey that size of audit fees is the most important factor, followed by competition, size of audit firm, tenure, provision of management advisory service and finally audit committee. More specifically, the study indicates that (1) larger size of audit fees, (2) audit firms operating in a higher level of competitive environments, 3) smaller audit firms, (4) audit firms serving a given client over a longer duration, (5) audit firms providing MAS, and, (6) the non-existence of an audit committee, are perceived as having a higher risk of losing independence. This study provides a basis for the profession to establish policies relating to auditor independence. Also, it may assist policy makers and other relevant international accounting agencies in their attempt towards the international harmonization of auditing standards. The major contribution of this paper is that it supplies recent evidence on factors influencing auditor independence from the viewpoint of Malaysian accountants.